Effects of Document Holder on Postural Neck Muscles Activity among Computer Users: A Preliminary Study. - Ambusam, Subramaniam; Omar, Baharudin; Joseph, Leonard; Deepashini, Harithasan (Journal of Research in Health Sciences, 2015)
BACKGROUND: Computer users are exposed to work related neck disorders due to repetitive movement and static posture for prolonged period. Viewing document and typing simultaneously are one of the contributing factors for neck disorders. METHODS: This preliminary study was conducted to evaluate the effects of the document holder on the postural neck muscles activity among computer users. Nine healthy participants with pre-defined inclusion and exclusion criteria were recruited for the study. Neck muscles activity were analyzed using the surface electromyography (EMG) in five different document location such as flat right, flat left, flat center, stand right and stand left during a 5 min typing task. RESULTS: The mean and standard deviation results showed a least amount of muscles activity using a document holder compared to without document holder. Nevertheless, the statistical analysis showed no significant differences between the using of a document holder. CONCLUSIONS: The effects of document holder on head excursion and neck muscle activity is recommended in clinical neck pain population.